Strategi Pengembangan Penangkapan Ikan Pelagis Kecil dengan Alat Tangkap Jaring Insang di Kabupaten Maluku Tenggara (The Development Strategy of Catching the Small Pelagic Fish by Gill Net Fishing Gear in Southeast Maluku Regency) - Elisabeth Cory Ohoiwutun (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2015)
The regency of southeast Maluku has a variety of promising fisheries and marine potency to be managed. Unfortunately, it has not been used properly. The fishing production volume of small pelagic in every season using gill net fishing gear has not been able to increase the income of fishermen in Southeast Maluku regency. The analytical methods used were the External Factor Evaluation (EFE), Internal Factor Evaluation (IFE), Internal-External (IE) and Strengths Weaknesses Opportunities Threats (SWOT) analytical matrix. These were used to develop the strategy of small Pelagic with gill net fishing gear. Based on the result, gill net fishing gear has a number of different production each season against every kind of small pelagic fish.Keywords: fishermen, gillnet, small pelagic fish